Perancangan Aplikasi Pengolahan Data Obat Pada Puskesmas Warmare Berbasis Web Menggunakan Framework CodeIgniter 3: Designing Medicine Data Processing Application At Warmare Community Health Center Using Framework CodeIgniter 3 - Alfi Syahriza; Julius Panda Putra Naibaho; Marlinda Sanglise (JISTECH: Journal of Information Science and Technology, 2024)
Warmare Community Health Center is a public health service institution expected to provide optimal services to the community. One important aspect of delivering health services is drug stock management. Currently, the processing and storage of drug data at Warmare Community Health Center are done manually. Manual processing of drug data has several drawbacks: it is less effective and efficient in managing drugs, and the data is at risk of being damaged or lost. The author has taken the initiative to create a web-based application for managing the entry and exit of drugs at Warmare Community Health Center using the CodeIgniter framework. The implementation of this drug management application aims to address the issues faced by Warmare Community Health Center. The application for managing drug entries and exits is developed using the Waterfall method and the CodeIgniter framework. The result is a successful development of a drug data management application for incoming and outgoing drugs at Warmare Community Health Center, designed to manage drug data available at the health center. This application provides drug management services, including drug stock data, incoming drug data, outgoing drug data, and drug data report printing.